The Effect of (Reading, Encoding, Annoting and Meditation) strategy in the Achievement in the Social Material of Second Stage Intermediate Students - Al-Khuzaie, Hamed Mashkoor Shaheid; Eubad, Muhamad Shallal (Al-Adab Journal, 2021)
The present research aims to identify, The Effect of (Reading, Encoding, Annoting, And Meditation) strategy in the Achievement in the Social Material of Second Stage Intermediate Students. The present research aims to identify, The Effect of (Reading, Encoding, Annoting, And Meditation) strategy in the Achievement in the Social Material of Second Stage Intermediate Students. To achieve the objective of the research, researcher put the following zero hypothesis: "There is no statistically significant difference at the level of significance (0,05) between the average degrees of the students of the experimental group who study according to the (Reading, Encoding, Annoting, and Meditation) strategy and the average degrees of the Control group students who study according to the traditional way in the achievement test". The researcher adopted a semi experimental approach and Experimental design with the Control group and the post test ,the experiment was applied to the research sample , which was represented by the students of the second grade in AL-Qaqa morning Governmental intermediate school for boys , which affiliated to general directorate of Education in Baghdad / The Second Resafah for the Academic year (2018-2019), which consisted of (66) students :(33) students in the experimental group which was studding according to the ( Reading , Encoding , Annoting , and Meditation) strategy , and the other (33) students resembled the control group which was studding according to the traditional way. The result of the test was calculated using the (T.test) for two independent samples where the result was: "There is a statistically significant difference at the level of significance (0,05) between the average degrees of the students of the experimental group who study according to the (Reading, Encoding, Annoting, and Meditation) strategy and the average degrees of the Control group students who study according to the traditional way in the achievement test, for the experimental group". Based on the result reached, the researcher concluded several conclusions, the most important of which are:- Teaching according to the (Reading, Encoding, Annoting, and Meditation) strategy, leads to the student's sense of the importance of reading as a key to this strategy, which lead them to improve this aspect continuously whether inside the class room or outside. The researcher also presented a number of recommendations: - The importance of exposing teachers of social materials adopting modern strategies, which proved to be effective in increasing the achievement of students. Also, the researcher suggests: - Identifying the effect of the (Reading, Encoding, Annoting, and Meditation) strategy in different stages of study.